KatakLarita as Educational Media to Increase Deaf Children’s Knowledge of Sexual Safety and Security Protection - Ni Luh Putu Yunianti Suntari; I Ketut Labir; Ni Made Yuni Gumala; Ni Putu Dessy Parmitha Sari; Ni Made Tariani; Dewa Gede Nata Raditya (Journal of Innovation in Educational and Cultural Research, 2025)
Children are vulnerable to sexual crimes around them. Children should know the dangers of sexual and how to protect themselves. Education related to sexual education and reproductive health in its implementation requires media that can be accessed by all children in Indonesia, including children with disabilities. This research aims to determine the effectiveness of educational media, KatakLarita, in increasing knowledge of sexual safety and security protection for deaf children. The respondents for this research were deaf children from four schools of special deaf in Bali. The method used in this research is paired t-test analysis, which aims to determine the difference in the level of knowledge before and after being given the procedure treatment. The results of the t-test show that the p-value score is 0.000004, and there is a mean difference between the pre-test and post-test data. The results of the Cohen-d score, which was greater than 0.8 (Statistical Power), concluded that the difference in the mean of the two data was significant enough so that it could be interpreted that the treatment given to this group was able to increase the participant's average knowledge. THE video educational media KatakLarita contributes to helping increase children’s knowledge, including deaf children, about efforts to protect themselves from sexual crimes.